2014
DOI: 10.7314/apjcp.2014.15.21.9249
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-loaded PLGA Nanoparticles Conjugated with Anti-P-glycoprotein Antibody to Overcome Multidrug Resistance

Abstract: Asian Pac J Cancer Prev, 15 (21), 9249-9258 IntroductionMultidrug resistance (MDR) is a major problem for the success of cancer chemotherapy and is closely associated with treatment failure in the most common forms of cancer, including lung, colon, breast, and cervical cancer (Chang, 2003). Overexpression of P-glycoprotein (P-gp), a 170-kDa plasma membrane transporter, has been identified as one of the major causes of drug resistance in several cancers. P-gp belongs to the superfamily of ATP-binding cassette (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…The mobile phase comprised 52% acetonitrile and 48% citric buffer (1% w/v citric acid, pH 3.0) and flow rate was set at 1 mL/min. Detection wavelengths for curcumin and analog 2A were 425 and 340 nm, respectively . Concentration of curcumin or analog 2A in serum was calculated and compared to standard curve (0‐3200 ng/mL).…”
Section: Methodsmentioning
confidence: 99%
“…The mobile phase comprised 52% acetonitrile and 48% citric buffer (1% w/v citric acid, pH 3.0) and flow rate was set at 1 mL/min. Detection wavelengths for curcumin and analog 2A were 425 and 340 nm, respectively . Concentration of curcumin or analog 2A in serum was calculated and compared to standard curve (0‐3200 ng/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Antiproliferative studies and downregulation of clonogenic potential of HeLa cells proved the better antitumor activity of PLGA NanoCur [87]. Similarly, Punfa et al [156] demonstrated the enhanced uptake and anticancer activity of CURloaded PLGA NPs in drug resistant cancer cells by conjugation with anti-Pgp [88,156]. The specific binding of CUR-NPs-APgp to KB-V1 cells was significantly higher than that to KB-3-1 cells.…”
Section: Polymeric Npsmentioning
confidence: 90%
“…Moreover, polylactic-co-glycolic acid nanoparticles containing curcumin were described in another study as having a higher cellular uptake and cytotoxic effect in cervical cancer cells, when compared to curcumin alone [50]. Furthermore, in a subsequent study, these authors conjugated the same nanoparticles (loaded with curcumin) with an anti-P-gp antibody in order to obtain a more targeted therapy [51]. These new nanoparticles presented a more pronounced cytotoxic effect against an MDR cervical cancer model than the nanoparticles without the P-gp antibody [51].…”
Section: Strategies For Overcoming the Limitations Of Curcuminmentioning
confidence: 99%
“…Furthermore, in a subsequent study, these authors conjugated the same nanoparticles (loaded with curcumin) with an anti-P-gp antibody in order to obtain a more targeted therapy [51]. These new nanoparticles presented a more pronounced cytotoxic effect against an MDR cervical cancer model than the nanoparticles without the P-gp antibody [51]. …”
Section: Strategies For Overcoming the Limitations Of Curcuminmentioning
confidence: 99%